Efeitos de um derrame simulado de petróleo sobre a comunidade planctônica costeira em Angra dos Reis (RJ) - Reynier, Marcia Vieira (2003)
Concern with the effect of oil spills in coastal regions resulting from the production, refining and transport of this product has been one of the priorities of the institutions working with this sector. Consequently, there is a large demand for research on the impacts of by accidents on the environment and, particularly, on natural communities. In the present study, a mesocosm experiment was used to evaluate the effects of a mixture of light Arabian and Russian oil with the chemical dispersant Corexit® 9500, over a coastal plankton community. The experiment was carried out in Rio de Janeiro and lasted 25 consecutive days. Three replicates were used as control, with only seawater, three were treated with 800 mL of petroleum and the other three were treated with the mixture 800 mL of petroleum and 80 mL of dispersant. The chemical alterations in the water were striking, especially the rise in the concentration of organic compounds. The results demonstrated a severe reduction of phytoplankton density, as a result of the addition of oil. There was also a change in the composition of the organism groups, with alteration of dominance of diatoms to phytoflagelates. Similar effect was found for the zooplankton. Both the oil and its mixture with dispersant resulted in a reduction of population densities and changes, or disappearance, of some components. Meroplanktonic organisms had a higher sensitivity to the acute effects of the oil and oil-dispersant mixture than holoplanktonic organisms. Copepods were resistant to the effects of oil and oil-dispersant mixture. Among the herbivores, Acartia lilljeborgi had greater resistance to the acute toxic effect of oil, whereas Pseudodiaptomus acutus was more resistant to the chronic effects of both oil and the mixture. Among carnivores, Oithona hebes appeared as a resistant species to both acute and chronical effects. Mesocosms were shown to be useful for investigating the effects of oil spills on marine environments since standardized laboratory tests with algae and invertebrate test-organisms corroborated the field findings.